NLRC5: A Potential Target for Central Nervous System Disorders - Zhang, Lu; Jiao, Cui; Liu, Lingjuan; Wang, Aiping; Tang, Li; Ren, Yi; Huang, Peng; Xu, Jie; Mao, Dingan; Liu, Liqun (Frontiers in Immunology, 2021)
Nucleotide oligomerization domain-like receptors (NLRs), a class of pattern recognition receptors, participate in the host’s first line of defense against invading pathogenic microorganisms. NLR family caspase recruitment domain containing 5 (NLRC5) is the largest member of the NLR family and has been shown to play an important role in inflammatory processes, angiogenesis, immunity, and apoptosis by regulating the nuclear factor-κB, type I interferon, and inflammasome signaling pathways, as well as the expression of major histocompatibility complex I genes. Recent studies have found that NLRC5 is also associated with neuronal development and central nervous system (CNS) diseases, such as CNS infection, cerebral ischemia/reperfusion injury, glioma, multiple sclerosis, and epilepsy. This review summarizes the research progress in the structure, expression, and biological characteristics of NLRC5 and its relationship with the CNS.